The Effect of Toxoplasmosis Infection on Interleukin-12Level During Human Maturity in Baghdad Province - R. Alkhanak, Yassmein; N. Alwachi, Sabah; H. Zghair, Khawla (Iraqi Journal of Science, 2023)
The goal of this study is to perceive the immunological sex-differences in puberty age who have positive anti-Toxoplasma Immunoglobulin-G (IgG) specific antibodies. From the first of November 2012 till the end of April 2013, 303 blood samples were collected from students in both genders (150 males and 153 females) were divided into two age groups: group (A) which included subjects with age range (12-15) years old and group (B) which included subjects with age range (16-19) years old. Serum samples were tested for toxoplasmosis infections by using Enzyme Linked Immunosorbent Assay (ELISA) for anti-Toxoplasma IgG antibodies test. The results revealed that 107/303 (35.31%) of the studied subjects showed seropositive toxoplasmosis, 60 males and 47 females of them with a high significant differences between toxoplasmosis infected and uninfected subjects. All serum samples were tested by using ELISA technique for detection of serum mean concentration of IL-12. This study showed high significant level of IL-12 in both males and females with latent toxoplasmosis in comparison with free-toxoplasmosis groups.